INVESTIGATIVE APPROACH IN IN TEACHING THE FUNDAMENTALS OF ARTIFICIAL INTELLIGENCE USING THE MAXIMA SYSTEM - Kohut, U.; Kobylnyk , Т. (Journal of Information Technologies in Education (ITE), 2020)
The article highlights the problem of the use of computer algebra systems (CAS) as a means of educational and research activities in the field of information and mathematical disciplines. The dynamism of the development of modern information technologies requires the integration of related disciplines on a common basis for them on a fundamental basis. The new type of intelligent systems should create the toolkit that will provide the educated person with the means of deeper mastery of the latest advances in computer science and science. The training of the fundamentals of artificial intelligence in the system of training computer science specialists at the pedagogical university plays a special role, since it combines both the fundamental concepts and principles of various mathematical and informational disciplines, and applied models and algorithms for their application. All this should lead to the search and introduction of new educational forms and technologies in education. One of such forms of organization of training is the research and design and research activity of students. Education at a pedagogical university should be a model of research work in the field of specialist work. The role of CAS in the preparation of bachelors in computer science and features of their pedagogical application in teaching the fundamentals of artificial intelligence are defined. The main characteristics of CAS MAXIMA are considered and the possibilities of using this system in the process of solving intellectual problems are given. The expediency of using the Maxima system for a research approach in the process of learning the fundamentals of artificial intelligence in a pedagogical educational institution, as well as determining the perspective ways of its introduction, is substantiated. The purpose of using CAS in the process of preparing future IT specialists is to build on them the ability to successfully use information technology in their professional activities, creative approach to solving non-standard tasks, deep mastering of fundamental fundamentals of disciplines. The prospect of further research is the expansion of a range of research tasks that can be solved with the use of computer mathematics systems.